PENGARUH TAKARAN BOKASHI FLY ASH TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BABY LOBAK (Raphanus sativus L) Var. Greenbow - Yanti Tristiana; Linlin Parlinah (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2015)
The research was conducted in the greenhouse Faculty of Agriculture, Winaya Mukti University Sumedang district, from April 2011 until June 2011, which is located at an altitude of 850 meters above sea level. The aim of research to study the effect of fly ash Bokashi on growth and baby yield of rapeseed varieties Greenbow. The design used in the study is a randomized block design, which consists of five treatments and five replications. Treatment trial is dose flay ash Bokashi, which is 0 tonnes ha-1, 5 ton ha-1, 10 ton ha-1, 15 ton ha-1 and 20 ton ha-1. The results showed that the fly ash Bokashi effect on plant height, number of leaves per plant, diameter and weight of sweet potatoes per plant. Award dose Bokashi fly ash 5 ton ha-1 showed equally good results by administering doses of fly ash Bokashi 10 ton ha-1, 15 ton ha-1 and 20 ton ha-1 on plant height, leaf number, diameter and weight of tuber turnip var. Greenbow, so enough with a dose of Bokashi fly ash 5 ton ha-1 can give good results for plant radishes var. Greenbow,